52-(3x-4)=x

Simple and best practice solution for 52-(3x-4)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 52-(3x-4)=x equation:


Simplifying
52 + -1(3x + -4) = x

Reorder the terms:
52 + -1(-4 + 3x) = x
52 + (-4 * -1 + 3x * -1) = x
52 + (4 + -3x) = x

Combine like terms: 52 + 4 = 56
56 + -3x = x

Solving
56 + -3x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
56 + -3x + -1x = x + -1x

Combine like terms: -3x + -1x = -4x
56 + -4x = x + -1x

Combine like terms: x + -1x = 0
56 + -4x = 0

Add '-56' to each side of the equation.
56 + -56 + -4x = 0 + -56

Combine like terms: 56 + -56 = 0
0 + -4x = 0 + -56
-4x = 0 + -56

Combine like terms: 0 + -56 = -56
-4x = -56

Divide each side by '-4'.
x = 14

Simplifying
x = 14

See similar equations:

| 2x+14+2x-7=55 | | 6a+9b=-7 | | 65-(2x+5)=3x | | -4+8x=-4(1+8x) | | -9=-8+r/16 | | 14-5m=5-8m | | 3x-34=12x-74 | | 90=4x-(2x-14) | | 3x-(x+26)=180 | | 5y-10=40 | | 4w-8w=28 | | 2x+(x-33)=90 | | -4=7x+1-8 | | 4(x-5)=x+4 | | 11n=10+16 | | 4x+(x+35)=90 | | (3x/(x-7))-((x+7)/x)=0 | | (3x/(x-7))-((x+7)/x) | | x-3=(5x-1)^1/2 | | 7g=6 | | 700-2x=50+2x | | -49.95-20x= | | x^2+4x-y=7 | | V=x(14-2x)(10-2x) | | 5(2x-7)=3(4x+9) | | 2x/5=x+6 | | 7m-3=3m+17 | | 4+10x=(x+9)4 | | x-5=20/5 | | 5x-1=-51 | | 9x+13=2x+174 | | t^3-5t^2+4t=0 |

Equations solver categories